Strategi Pembina Galanggang Lubuk Aro dalam Pembinaan Keagamaan Islam Remaja - Ilman Suhdi; Murniyetti Murniyetti (Program studi Keagamaan Islam, 2021)
This study aims to determine the Strategy of Guiding Troubled in Islamic Religious Guidance for Teenagers in North Padang Mantinggi Village, Rao District, Pasaman Regency. This research is a type of field research using qualitative methods. Sources of data were taken from three informants consisting of coaches of trouble, five parents of teenagers, and fifteen members of teenagers using purposive sampling technique. Research data were taken through in-depth interviews with all informants. The results showed that the Guidance Strategy for Guidance in Islamic religious development for adolescents in Padang Mantinggi Utara Village, Rao District, Pasaman Regency, was by carrying out positive activities favored by teenagers, such as soccer and pencak silat training for teenage boys, marawis training. or tambourine and rhythm training for teenage girls. So that with positive activities it will be easier to direct teenagers to explore religious issues by participating in regular recitations in the hope that teenagers can have better knowledge of the Islamic religion